2021
DOI: 10.1101/2021.02.22.432327
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA reconciles morphology and colouration in the drunk blenny genusScartichthys(Teleostei: Blenniidae) and provides insights into their evolutionary history

Abstract: The blenniids of the genus Scartichthys represent key herbivore species of central and south American Pacific coastal reefs. Yet Scartichthys spp. remain difficult to identify in the field, especially across the c.a 6000 km where three of the four currently accepted species are known to occur in sympatry. The main diagnostic characters from traditional taxonomy that have been used to revise this genus are indeed elusive. At the same time, species can display multiple colour patterns in the field, depending on … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…This might indicate that such closely related species might be redundant to one another in terms of ecological roles. Second, species delimitations among the fish families tested might be based on traits and features that might not be captured by our overall body shape analysis (Delrieu-Trottin et al, 2021). Nevertheless, our analyses also demonstrated that five families show greater levels of observed functional diversity than expected from species richness alone.…”
Section: Pleuronectidaementioning
confidence: 75%
See 1 more Smart Citation
“…This might indicate that such closely related species might be redundant to one another in terms of ecological roles. Second, species delimitations among the fish families tested might be based on traits and features that might not be captured by our overall body shape analysis (Delrieu-Trottin et al, 2021). Nevertheless, our analyses also demonstrated that five families show greater levels of observed functional diversity than expected from species richness alone.…”
Section: Pleuronectidaementioning
confidence: 75%
“…This might indicate that such closely related species might be redundant to one another in terms of ecological roles. Second, species delimitations among the fish families tested might be based on traits and features that might not be captured by our overall body shape analysis (Delrieu‐Trottin et al, 2021). For example, internal structures not obvious from external analyses, such as gill raker counts and lengths, dental incisor counts, coloration patterns and behavioural adaptions to habitat use (e.g., spawning areas or depths), might not necessarily manifest as visible functional features easily captured by geometric morphometric body shape analyses.…”
Section: Discussionmentioning
confidence: 99%